2018
DOI: 10.1097/ccm.0000000000003379
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors on Hospital Arrival for Acute Respiratory Distress Syndrome Following Pediatric Trauma*

Abstract: We provide the first description of the incidence of and risk factors for acute respiratory distress syndrome among pediatric trauma patients. Improved understanding of the risk factors associated with acute respiratory distress syndrome following pediatric trauma may help providers anticipate its development and intervene early to improve outcomes for severely injured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…We specifically examined PARDS because children hospitalized with TBI are at risk for PARDS owing to a variety of factors, including intracranial hypertension, severe systemic inflammation, direct traumatic lung injury, and secondary lung injury from aspiration or pneumonia. 21,22 It is thus reasonable to expect that many critically injured children with TBI, especially those with PARDS or other pulmonary pathologic characteristics, may have an elevated alveolar dead space fraction and thus lower Pa co 2 -EtCO 2 agreement. This study identified PARDS as an independent factor associated with a lower likelihood of Pa co 2 -EtCO 2 agreement, which provides new information on the utility of capnography among children with TBI with concurrent lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically examined PARDS because children hospitalized with TBI are at risk for PARDS owing to a variety of factors, including intracranial hypertension, severe systemic inflammation, direct traumatic lung injury, and secondary lung injury from aspiration or pneumonia. 21,22 It is thus reasonable to expect that many critically injured children with TBI, especially those with PARDS or other pulmonary pathologic characteristics, may have an elevated alveolar dead space fraction and thus lower Pa co 2 -EtCO 2 agreement. This study identified PARDS as an independent factor associated with a lower likelihood of Pa co 2 -EtCO 2 agreement, which provides new information on the utility of capnography among children with TBI with concurrent lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings of this study of hospitalized pediatric patients with TBI are that (1) We specifically examined PARDS because children hospitalized with TBI are at risk for PARDS owing to a variety of factors, including intracranial hypertension, severe systemic inflammation, direct traumatic lung injury, and secondary lung injury from aspiration or pneumonia. 21,22 It is thus hours of admission should still be considered the optimal modality to monitor CO 2 levels, especially when ongoing resuscitation may be needed and optimizing cerebral perfusion is critical. Given the focus on prevention of prophylactic hypocarbia in severe pediatric TBI, these findings suggest a need for the Brain Trauma Foundation guidelines to address arterial measurements for PaCO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Approximately 1.8% of children included in the NTDB admitted to an intensive care unit (ICU) following trauma develop ARDS. 2 Those with ARDS experience a significantly higher risk of morbidity and mortality than children with comparable injury type and severity without ARDS. 3 Although these data offer important insights into the impact of ARDS on outcomes after pediatric trauma, there are limitations to using the NTDB to study ARDS in children.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with other pediatric studies, which report a low incidence of ARDS in non-trauma patients. Furthermore, the rate of ARDS has previously been shown to be low specifically in pediatric trauma patients with Roulet et al finding an incidence of 0.5% of all pediatric trauma admissions and Killen et al demonstrating an incidence of 1.8% of all pediatric patients admitted to an ICU [34,35]. Lee et al postulated the lower rate of ARDS and associated mortality in younger patients is due to greater capacity for repair, and altered cytokine burden including interleukin-1 and -8, and tissue necrosis factor alpha [36].…”
Section: Discussionmentioning
confidence: 99%